Baseline and decline in device‐derived activity level predict risk of death and heart failure in patients with an ICD for primary prevention. Issue 8 (27th June 2020) - Jamé, Sina; Cascino, Tom; Yeow, Raymond; Ananwattanasuk, Teetouch; Ghannam, Michael; Coatney, John; Shantha, Ghanshyam; Chung, Eugene H.; Saeed, Mohammed; Cunnane, Ryan; Crawford, Thomas; Latchamsetty, Rakesh; et al.
Abstract: Background: Implanted defibrillators are capable of recording activity data based on company‐specific proprietary algorithms. This study aimed to determine the prognostic significance of baseline and decline in device‐derived activity level across different device companies in the real world. Methods: We performed a retrospective cohort study of patients (n = 280) who underwent a defibrillator implantation (Boston, Medtronic, St. Jude, and Biotronik) for primary prevention at the University of Michigan from 2014 to 2016. Graphical data obtained from device interrogations were retrospectively converted to numerical data. The activity level averaged over a month from a week postimplantation was used as baseline. Subsequent weekly average activity levels (SALs) were standardized to this baseline. SAL below 59.4% was used as a threshold to group patients. All‐cause mortality and death/heart failure were the primary end‐points of this study. Results: Fifty‐six patients died in this study. On average, they experienced a 50% decline in SAL prior to death. Patients (n = 129) who dropped their SAL below threshold were more likely to be older, male, diabetic, and have more symptomatic heart failure. They also had a significantly increased risk of heart failure/death (hazard ratio [HR] 3.6, 95% confidence interval [95% CI] 2.3‐5.8, P < .0001) or death (HR 4.2, 95% CI 2.2‐7.7, P < .0001) compared to those who had sustained activity levels. Lower baseline activity level was also associated with significantly increased risk of heart failure/death and death. Conclusion: Significant decline in device‐derived activity level and low baseline activity level are associated with increased mortality and heart failure in patients with an ICD for primary prevention.